STUDY TRIES TO DISCOVER THE STYLES IN THE NOVEL "SHABUN AREN YAHMILU BUNDAQAIYATAIN"( A YOUNG NAKED BOY CARRYING TWO GUNS) BY THE AUTHOR ABDUL-KAREEM YAHAYA AL-ZEBARY - Mustafa, Rashad Kamal (Journal of Duhok University, 2018)
The present study tries to discover the styles in the novel "shabun aren yahmilu bundaqaiyatain"( a young naked boy carrying two guns) by the author Abdul-Kareem Yahaya Al-Zebary. Through which, he prescribes the story-novel style with diagnosing these styles and their uniqueness and their important semantic and mental dimensions. The writer used those styles to affect the reader and deliver his messages. It is a real historical novel which reflects the real society of Kurds under the autocratic social and feudal regimes as well as the dictatorial political regimes that governed Iraq during Kingdom and republic times. The writer tried to avoid pure historical way by using artistic and technical styles in order to get rid of literal and boring reality and to add literary styles to the language of the novel. The writer was able to, by those styles which are employed aesthetically, to express deep thoughts and good feelings, love ,peaceful and cultural values as well as refusing violence, extremism and wars. The hero of the novel (Dler) decided to join Peshmerga forces because he is no longer affording oppression and autocracy while he had a great love towards his beloved (Chavsheen). Therefore, the love and war feelings were overlapped in the novel embodying the conflict between life represented in love towards Dler and death represented in fighting. The present paper is important due to the fact that it is a modern novel published recently (2015) and it has never been studied before. The research observed three styles used intensively in the novel trying to know their aesthetic and mental levels through three sections. They are: symbolic approach, rhetorical images and paradox.